Research methods for business students - SAUNDERS, M (Pearson, 2012)
This fully revised 9th edition provides excellent coverage guiding you through the entire process, from deciding on a research topic to writing your dissertation or project and presenting your academic poster. By taking a transactional approach, the textbook will help you choose your project through critically reviewing the literature and designing your research, answering key questions such as: How do I generate a research idea and design my research, how do I review the literature critically, why is research philosophy relevant to my research, How do I collect and analyse my data, when and what do I need to write, how can I do research virtually.This comprehensive guide to conducting research will support you step-by-step at every stage of the process, offering a wealth of thought-provoking features and activities, such as tips and tricks from other students' experiences on their research projects and a complete glossary of terms. It provides case studies, news, and articles based on the latest virtual and face-to-face methods, discussing how research is used in practice within organisations worldwide. Written by experts in the field, this resource guides you through developing your research skills by taking a clear, concise, and transparent approach, helping you complete and successfully present your research." -- Provided by Publisher